Carrying Capacity and Institutional Analysis of Floating Net Cages in Jatiluhur Reservoir - Simangunsong, Nurmala Fitri; Hidayat, Aceng (Sustinere: Journal of Environment and Sustainability, 2017)
The cultivation of freshwater fish with floating net-cages system in the area of Jatiluhur Reservoir, Purwakarta Regency has increased in quantity. It results in the pollution and sedimentation because of development of floating net-cages business which exceeds the carrying capacity of the reservoir. This research aimed to analyze the carrying capacity of Jatiluhur Reservoir, conduct the institutional analysis, and analyze the perception of stakeholders involved in floating net-cages management in Jatiluhur Reservoir. Interview and literature review were used as the primary and secondary data collection methods. The results showed that the number of floating net-cages units in accordance with the carrying capacity of Jatiluhur Reservoir was amounted to 6,838 floating net-cages. For the management of floating net-cages in Jatiluhur Reservoir, the Department of Animal Husbandry and Fisheries of Purwakarta Regency and Perum Jasa Tirta II have important roles in formulating regulations and providing guidance to the fish farmers. The transaction costs spent on formulating regulations and providing guidance by the Regional Government of Purwakarta Regency was amounted to Rp 689,400,000 per year while Perum Jasa Tirta II spent amounted to Rp 70,107,900 per year. Although stakeholders have common perception on ecological and economic aspects, they have different perception on the management aspects of floating net-cages.